2009
DOI: 10.1105/tpc.109.067603
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Nitrate Transporter NRT1.7, Expressed in Phloem, Is Responsible for Source-to-Sink Remobilization of Nitrate  

Abstract: Several quantitative trait locus analyses have suggested that grain yield and nitrogen use efficiency are well correlated with nitrate storage capacity and efficient remobilization. This study of the Arabidopsis thaliana nitrate transporter NRT1.7 provides new insights into nitrate remobilization. Immunoblots, quantitative RT-PCR, b-glucuronidase reporter analysis, and immunolocalization indicated that NRT1.7 is expressed in the phloem of the leaf minor vein and that its expression levels increase coincidental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
245
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(270 citation statements)
references
References 64 publications
(75 reference statements)
10
245
0
9
Order By: Relevance
“…Previous reports have shown that NRT1.8/NPF7.2 and NRT1.7/ NPF2.13 from the NRT1/PTR family play roles in NO 3 2 removal from the xylem and NO 3 2 loading into the phloem, respectively (Fan et al, 2009;Li et al, 2010). Thus, we examined the phenotypes of the nrt1.7 and nrt1.8 mutants under the LK condition.…”
Section: Nrt15 Function Does Not Depend On Skormentioning
confidence: 99%
“…Previous reports have shown that NRT1.8/NPF7.2 and NRT1.7/ NPF2.13 from the NRT1/PTR family play roles in NO 3 2 removal from the xylem and NO 3 2 loading into the phloem, respectively (Fan et al, 2009;Li et al, 2010). Thus, we examined the phenotypes of the nrt1.7 and nrt1.8 mutants under the LK condition.…”
Section: Nrt15 Function Does Not Depend On Skormentioning
confidence: 99%
“…So far, both the low-affinity nitrate transporter NRT2.7 and the chloride channel, CLCa, were identified as responsible for shortdistance nitrate translocation into vacuoles (De Angeli et al, 2006;Chopin et al, 2007). For long-distance transport, recent studies found that NRT1.5 represents a major mechanism for loading nitrate into xylem vessels (Lin et al, 2008) and NRT1.7 for loading nitrate into the phloem (Fan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Root-to-shoot nitrate transport is probably governed by three members of AtNRT1 family: two closely related transporters NRT1.5 and NRT1.8, are responsible for loading or retrieving nitrate from xylem sap, respectively, whereas root stele-expressed AtNRT1.9 is involved in the loading of nitrate into the root phloem to enhance downward nitrate transport in roots (Wang and Tsay 2011). The remaining AtNRTs operate in shoots, where they are involved in nitrate storage in leaf petioles (NRT1.4), NO 3 − translocation from maternal tissue to developing embryos (NRT1.6) or the remobilization of NO 3 − from older to younger leaves (NRT1.7) (Chiu et al 2004;Almagro et al 2008;Fan et al 2009). The molecular features of nitrate transport within plants and the regulation of this process have been thoroughly studied mostly in the model plant Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%